STRUKTUR FUNDAMENTAL ILMU PENGETAHUAN MENURUT ARCHIE JOHN BAHM - Umu Salma (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
Philosophy of science which is a branch of philosophy, has a special object in its study, namely science. In re-establishing the meaning of science, the philosophy of science can be interpreted as a philosophical foundation that acts as the basic framework of science itself. According to the figure of Archie J. Bahm in his article What is science ?, there are six basic components that are fundamental in the building of science, including: problems, attitudes, use of scientific methods, activities, conclusions, and influences. Based on this information, the author's interest arises to outline his idea, how true the fundamental structure of science according to Archie John Bahm who throughout his description, always has a relationship with elements of humanity and also social. Keywords: structure, fundamentals, science.